Enabling learning through technology: some institutional imperatives - Audrey McCartan; Barbara Watson; Janet Lewins; Margaret Hodgson (Association for Learning Technology, 1995)
The imminent completion of many Teaching and Learning Technology Programme (TLTP) projects means that a considerable number of courseware deliverables will soon be available to Higher-Education (HE) institutions. The Higher Education Funding Council's intention in funding the Programme (HEFCE Circulars, 8/92, 13/93) was to ensure their integration into academic curricula by providing institutions with an opportunity to review their 'teaching and learning culture' with regard to the embedding of learning technology within their institutional practice. Two recent workshops, conducted with a representative sample of newly appointed academic staff in connection with the evaluation of materials to be included in a staff development pack whose purpose is to encourage the use of IT in teaching and learning (TLTP Project 7), strongly suggested that the availability of courseware alone was insufficient to ensure its integration into educational practice. The establishment of enabling mechanisms at the institutional level, as well as within departments, was crucial to ensure the effective use of learning technology.